Associations of Child Maltreatment and Intimate Partner Violence With Elder Abuse in a US Chinese Population - Dong, XinQi (JAMA Intern Med, 2019)
IMPORTANCE: People who have experienced abuse as a child or violence with an intimate partner might have higher odds of being abused again, but this has been insufficiently investigated regarding elder abuse. More conclusive evidence might be critical to assessment and prevention strategies. OBJECTIVE: To examine the associations of child maltreatment and intimate partner violence with elder abuse. DESIGN, SETTING, AND PARTICIPANTS: Cross-sectional data of 3157 community-dwelling US Chinese older adults (60 years or older) in Chicago, Illinois, were collected during 2011 through 2013. EXPOSURES: Cases of child maltreatment and intimate partner violence. MAIN OUTCOMES AND MEASURES: Cases of elder abuse. RESULTS: Of the 3157 US Chinese older adults included in the study, 1328 (42.1%) were men, and the mean (SD) age was 72.8 (8.3) years. The prevalence of elder abuse, child maltreatment, and intimate partner violence in the cohort was 15.2%, 11.4%, and 6.5%, respectively. After adjusting for sociodemographic variables, health status, quality of life, and health change, individuals reporting child maltreatment had increased odds of intimate partner violence (13.4% vs 5.6%; adjusted odds ratio [aOR], 2.57; 95% CI, 1.78-3.71) and elder abuse (25.2% vs 13.8%; aOR, 2.08; 95% CI, 1.57-2.75) than those not reporting child maltreatment. Individuals reporting intimate partner violence had increased odds of elder abuse than those not reporting intimate partner violence (48.8% vs 12.9%; aOR, 5.53; 95% CI, 4.01-7.64). CONCLUSIONS AND RELEVANCE: Prior abuse across major lifespan stages is associated with higher odds of elder abuse. Health care professionals should be more aware of the possibility of abuse when there is a known history of violence in a patient and consider the cumulative effect of violence among those exposed to elder abuse.